Accountability mechanisms in community-driven reconstruction in eastern Democratic Republic of Congo. Issue 1 (2nd January 2018) - Kyamusugulwa, Patrick Milabyo; Hilhorst, Dorothea; Jacobs, Carolien
ABSTRACT: A lack of accountability is often considered a root cause of conflict. Many post-conflict reconstruction efforts therefore aim to enhance accountability between authorities and the population through community-driven reconstruction programmes. This article examines the accountability mechanisms in the Tushiriki community-driven reconstruction programme in eastern Democratic Republic of Congo. The ethnographic research found little impact of formal programme accountability. Rather, accountability was shaped differently and had its own context-specific meaning. To make accountability more sustainable, stronger embeddedness in local institutions and more appropriate translations of abstract concepts into the local context are needed.